Excel VBA 24-hour trainer - Urtis, Tom.; Safari eBooks (Hoboken, N.J. : Wiley, 2011)
Presents information on using Microsoft's Visual Basic for Applications (VBA) programming language to customize the spreadsheet program Excel.
Description based on print version record.
"Wrox programmer to programmer." --Cover.
Includes index.
Keywords: Microsoft Excel (Computer file); Microsoft Visual Basic for applications; Electronic spreadsheets; Business -- Computer programs; Electronic books